The relationship between safety management practices and safety compliance behaviour among laboratory personnel in the northern region of peninsular Malaysia - Nurul Fatin, Md Rodzi (2020)
This study aims to determine the relationship between safety management practices and safety compliance behaviour among laboratory personnel in Northern region. The safety management practices are management commitment, safety training, safety communication and feedback, employees’ involvement, safety rules and procedures and safety promotion policies. The quantitative survey using questionnaires adapted from the previous studies was used in this study. A total of 134 laboratory personnel at five laboratory in Northern region were involved in this study. Data were analyzed using descriptive statistics via IBM SPSS Statistics.From the study, management commitment, workers involvement, safety training, safety communication and feedback and safety promotion policies were not have significant relationship with safety compliance behaviour among laboratory personnel. Meanwhile, only safety rules and procedure have significant relationship between safety compliance behaviour among laboratory personnel. Finally, managerial and theoretical implications are discussed and recommendations for future researchers.